Out-of-Pocket Cost Is a Barrier to Therapeutic Drug Monitoring in Inflammatory Bowel Disease - Campbell, James P. (Dig Dis Sci, 2017)
BACKGROUND: Therapeutic drug monitoring (TDM) is increasingly performed to optimize biologic therapy in inflammatory bowel disease (IBD). However, patients and physicians may be reluctant to perform TDM due to concerns related to potential out-of-pocket costs. AIMS: The aim of this study was to evaluate patient understanding and attitudes toward TDM in different clinical scenarios with and without potential out-of-pocket costs. METHODS: Adult IBD patients at a tertiary gastroenterology clinic were anonymously surveyed from March to September 2016 to assess their understanding of and willingness to undergo TDM in a variety of clinical scenarios, both with and without a potential out-of-pocket cost. Responses were analyzed for associations with changes in attitudes if out-of-pocket costs were involved. RESULTS: Of 118 completed surveys, 68.2% of patients were aware of or had previously undergone TDM. Patient willingness to undergo TDM was high both with and without potential out-of-pocket costs (70 and 98%, respectively); however, patients were significantly less willing with out-of-pocket cost (p < 0.01). Higher disease-related quality of life scores, as measured by the short inflammatory bowel disease questionnaire (SIBDQ), was significantly associated with an increased willingness to assume a potential out-of-pocket cost (p = 0.007). CONCLUSIONS: Overall, patients understand and are willing to undergo TDM in certain potentially beneficial clinical scenarios, however, are significantly less willing if paying out-of-pocket. A higher SIBDQ score was associated with an increase in willingness to undergo TDM when out-of-pocket cost was involved. Physicians should discuss TDM with their patients in order to make an informed and personalized treatment decision.